2012
DOI: 10.1155/2012/636824
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticojejuno Anastomosis after Pancreaticoduodenectomy: Brief Pathophysiological Considerations for a Rational Surgical Choice

Abstract: Introduction. The best pancreatic anastomosis technique after pancreaticoduodenectomy (PD) is still debated. Pancreatic fistula (PF) is the most important complication but is also related to postoperative bleedings and pancreatic remnant involution. We support pancreaticojejuno anastomosis (PJ) advantages describing our technique with brief technical considerations. Materials and Methods. 89 consecutive patients underwent PD with suprapyloric gastric resection and double loop reconstruction. Pancreaticojejunal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…The popularity of sealant patches in pancreatic surgery is mainly related to the assumption that these products may reduce the overflow of pancreatic juice from the anastomosis during the first few days after surgery, thereby reducing biochemical leakage and its sequelae, such as inflammatory retention and late haemorrhage. The present results do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 91%
“…The popularity of sealant patches in pancreatic surgery is mainly related to the assumption that these products may reduce the overflow of pancreatic juice from the anastomosis during the first few days after surgery, thereby reducing biochemical leakage and its sequelae, such as inflammatory retention and late haemorrhage. The present results do not support this hypothesis.…”
Section: Discussioncontrasting
confidence: 91%
“…6 For this reason, our research team carried out a Roux-en-Y retrocolic reconstruction with anastomosis of the isolated Roux limb (ie, first jejunal loop) to the stomach and single Roux limb (ie, second jejunal loop) to the pancreatic stump and hepatic duct. 7 In accordance with the work of Eshuis et al and the results of a recent metaanalysis, 8 we found that after PD, the route of the gastro/duodenojejunal anastomosis with respect to the transverse colon or type of reconstruction (Billroth I or Billroth II) conducted are not responsible for the difference in the prevalence of DGE, and that the impact of reconstructive methods on DGE is related primarily to angulation or torsion of the gastro/duodenojejunostomy. 9 Then, not necessarily an antecolic but rather a ''straight'' reconstruction of the alimentary tract may prevent DGE after PD.…”
supporting
confidence: 88%
“…The considerable variety and heterogeneity of anastomotic methods challenges the performance of high quality RCTs in order to properly compare these different reconstruction methods after pancreatoduodenectomy. 12,[58][59][60] Extensive experience or unfamiliarity with one of the selected anastomotic techniques as well as a learning curve phenomenon may bias the results. Moreover, pancreatic anastomosis techniques are generally described in single-surgeon or singleinstitution studies often reporting low POPF rates of their preferred pancreatic anastomosis.…”
Section: Hpbmentioning
confidence: 99%